Micro feeding machines in the dairy industry - Kass, Carl (Kansas State University, 2018)
Micronutrient machines have been used successfully in the beef industry, however, their use was mostly for the addition of antibiotics into the rations. Their use in the dairy industry has been very limited. Feed cost is over 50% of the total cost on a typical dairy farm, thereby creating an area where minor changes in cost per cow can impact the bottom line. Because of the high feed cost on dairy farms, income over feed cost (IOFC) is one of the bench marks as to the overall farm financial health. The feed rations also impact animal health incidences and reproduction efficiencies. Micro machines can add small amounts of a desired nutrient or product, generally less than 56 grams (± 2 oz) into the cattle's daily total mixed rations (TMR). These micronutrients are generally expensive, and their inclusion into the rations of only cows that need that particular micronutrient is one benefit of a micro machine. Micro machines also take out the human error of mixing small accurate amounts and can easily track inventories. Benefits also include the control of on-farm shrink through dust control, and environmental stewardship of resources. Lastly, by creating options to accurately add micronutrients, milk production may be increased and health incidences reduced. The dairy industry is a virtually an untapped field for this technology and this research will explore if there is a benefit from their use. As feeding systems have evolved and milk production has continued to climb, innovative technologies will continue to be implemented. Increased financial pressures will also continue to cause producers to become more efficient with their resources. As production increases in any field, fine tuning of inputs becomes more exact. The rumen inner workings and how feedstuff blends affect rumen micros and the pH levels is an area in which there is much research completed, however, much more is still needed. The addition of micro machines to fine tune rations for dairy farms TMR rations can be a profitable way to manage income over feed cost, not only by saving money spent on micronutrients but by increasing production and reducing herd health incidences.
Keywords: Micronutrients; Price sensitivity; Methionine